Towards a feminist global ethics. Issue 1 (31st December 2022) - Tong, Rosemarie
ABSTRACT: In this article, I explain what makes a global bioethics "feminist" and why I think this development makes a better bioethics. Before defending this assertion explicitly, I engage in some preliminary work. First, I attempt to define global bioethics, showing why the so-called feminist sameness-difference debate [are men and women fundamentally the same or fundamentally different?] is of relevance to this attempt. I then discuss the difference between rights-based feminist approaches to global bioethics and care-based feminist approaches to global bioethics. Next, I agree with a significant number of feminist bioethicists that care is a more fundamental moral value and practice than justice. Finally, I conclude that feminists' insights about care, even more than rights, can bring us closer to achieving an inclusive, diverse, and fair feminist global bioethics.